PERANAN KEPALA SEKOLAH DALAM PELAKSANAAN PENDIDIKAN KARAKTER DI SEKOLAH MENENGAH PERTAMA (SMP) DI KECAMATAN SINDUE - Afriadi, Afriadi (Katalogis, 2017)
This research aims to describe (1) the condition of the character of students, (2) functions, adjustment, and the process undertaken in the implementation of the principal character education, (3) development of a flagship character performed the principal. Methods used is a descriptive with a descriptive qualitative data analysis techniques of interactive models, Miles and Huberman, and Likert scale question form analysis. The population in this study is a entire principal a number of 5 persons, a number of 118 teachers, and students to a number of people at 1,041 person in Sindue Sub-district. Sample. The number of samples of the principal amounts of 5 people using sampling a number of principal samples are saturated, 280 students are divided into 56 school 5 pupils by school using random sampling techniques, sample teacher as much as 90 people are divided into 18 schools teachers by school using random sampling techniques. Engineering data retrieval using descriptive analysis and interview guide scale Likert. The results showed that: first, the character of the students in junior high se Sindue Sub-district is divided into (1) characters are weak, (2) strong characters , (3) the character of ugly, (4) good characters. Second, the function, and the process of adjustment, in character education is done in General by the principal, the difference is how to encourage teachers and students in carrying outactivities of character education in their respective junior high school. Third, the pre-eminent character development done by the head of the junior school is generally done by dissemination to the program the extracurricular activities. The thing that distinguishes is awarding tasks in a community environment is only done by the head of the junior school the country 5 Sindue.